Aktivitas Antimikroba Ekstrak Daun Dan Buah Ginje(Thevetia peruviana) TERHADAP Staphylococcus aureus Dan Candida albicans Secara In Vitro - Pratama, Eka Yudha, Dra. Titik Suryani, M.Sc (2015)
Staphylococcus aureus and Candida albicans is pathogenic microbes that cause infections in humans. Plants yellow oleander (Thevetia peruviana) is a medicinal plant traditionally used as antifungal, antibacterial, and insecticides. The purpose of this study to compare the antimicrobial activity of extracts of leaves and fruit ginje (Thevetia peruviana) against Staphylococcus aureus and Candida albicans. This research method using a completely randomized design (CRD) with two factors, one factor is the type of microbe Staphylococcus aureus: Candida albicans and 2 factors, namely leaf extract : fruit extract with fruit extracts infuse extraction method . The results showed that the extract of the fruit has antimicrobial activity is greater than leaf extract on the growth of Staphylococcus aureus and Candida albicans. This is caused by the presence of Thevetin (steroidal glycosides) in the fruit, which has the ability to work very specific and inherent. Character extract of the leaves and fruit Ginje have antimicrobial inhibition with strong category. Keyword : antimicrobial , leaf and fruit extracts Thevetia , microbes.